Collaboration of Teachers and Parents in the Formation of Students’ Virtuous Morality - Mutik Fadhilah; Muhammad Djakfar; Zulfi Mubaraq; Juvinal Ximenes Guterres (Program Studi PGMI UIN Salatiga, 2022)
Teachers and parents must be synchronous and integrated into providing education to students, especially for the moral formation of students. This study describes the program, form, and implications of cooperation between teachers and parents in forming student morality at SDI Mohamad Hatta and MI Al-Marhamah, Malang. This research uses a qualitative approach using case studies and multi-site designs. The research population at SDI Mohammad Hatta was 30 teachers, 368 parents, and 368 students, with a sample of 15 teachers, 50 parents, and 50 students. At MI Al Marhamah, on the other hand, there are 14 teachers, 150 parents, and 150 students with a sample of 7 teachers, 50 parents, and 50 students. Interviews, observations, and document search were used for data collection. The findings of this study are that there are three collaborative programs between teachers and parents in forming students' noble character, namely parenting, home visits, and self-development project programs. Collaboration between teachers and parents takes the form of activities to develop the learning process, talent, mentality, and culture. The implications of the cooperation program for teachers are to understand students' backgrounds better, appreciate parents' efforts in moral formation, and improve communication with parents. As for parents, they better understand their role, gain new perspectives about schools and teachers, and appreciate the role of teachers more. Students will have a more positive and quality personality. This research is expected to be able to provide new input and discourse to educational institutions in collaborating between teachers and parents in the formation of commendable morals of students as well.